2020
DOI: 10.3389/fmicb.2020.00555
|View full text |Cite
|
Sign up to set email alerts
|

Anti-MRSA Activity of Actinomycin X2 and Collismycin A Produced by Streptomyces globisporus WA5-2-37 From the Intestinal Tract of American Cockroach (Periplaneta americana)

Abstract: Methicillin-resistant Staphylococcus aureus (MRSA) is recognized as one of the serious pathogen that causes acquired infections worldwide. Its emerging need to discover novel, safe and potent anti-MRSA drugs. In this study, primary screening by anti-MRSA activity assay found one strain WA5-2-37 isolated from the intestinal tract of Periplaneta americana, exhibited great activity against MRSA ATCC 43300. The strain WA5-2-37 produced actinomycin X 2 and collismycin A which showed strong inhibition of MRSA with m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 38 publications
(33 reference statements)
0
14
0
1
Order By: Relevance
“…americana and was found to match the insect clade of S. albidoflavus (Cheng et al 2015;Matarrita-Carranza et al 2017). The antibiotics actinomycin X2 and collismycin A, both with activity against methicillin-resistant S. aureus (MRSA), were purified from 40 L of S. globisporus WA5-2-7 culture broth (Chen et al 2020), highlighting the biotechnological potential of cockroach-associated Streptomyces.…”
Section: Actinobacteriamentioning
confidence: 99%
See 1 more Smart Citation
“…americana and was found to match the insect clade of S. albidoflavus (Cheng et al 2015;Matarrita-Carranza et al 2017). The antibiotics actinomycin X2 and collismycin A, both with activity against methicillin-resistant S. aureus (MRSA), were purified from 40 L of S. globisporus WA5-2-7 culture broth (Chen et al 2020), highlighting the biotechnological potential of cockroach-associated Streptomyces.…”
Section: Actinobacteriamentioning
confidence: 99%
“…Very recently, a species of Streptomyces producing actinomycin X 2 and collismycin was isolated from the gut of Pe. americana (Chen et al 2020). Bacteria in cockroaches are likely to produce antimicrobial compounds less toxic than those found in soil bacteria, because the host must survive exposure to these agents.…”
Section: General Outlook For Cockroach-associated Bacteriamentioning
confidence: 99%
“…Several species of Streptomyces have been used for the control of soil phytopathogens (Ling et al, 2020). Among the bioactive compounds they produce are: hydrolytic enzymes and actinomycins, which are antibiotics belonging to the chromopeptide lactone family that function as growth inhibitors (Chen et al, 2020). Nocardiopsis species exhibit antifungal activity against Fusarium species and produce various antimicrobial metabolites (Intra et al, 2011).…”
Section: In Vitro Antagonism Tests Of Marine Actinomycetes Against F ...mentioning
confidence: 99%
“…Besides, in the existing research reports of insect microorganisms, most of them focus on pest control, biological agents, ecological protection and ecological diversity, and the study on antimicrobial activity of their secondary metabolites is less (Dantur et al 2015 ; Guo et al 2017 ; Zheng et al 2020 ). Our previous study showed that the endobacteria in the intestinal tract of Periplaneta americana exhibited various antimicrobial activities against all tested pathogens (Fang et al 2018 ; Chen et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%